The spiritual, educational and social functions of mosques during COVID-19 pandemic - Abdul Rahman, Shukran (IIUM Emotional and Psychological Support Site, 2020)
The collective aspects of Ramadhan, which were experienced in our yesteryears, have to be substituted with other activities. The break-of-fast or iftar session with our fellow brothers and sisters, as well as congregational prayers including the tarawih at mosques are replaced with in-house iftar and congregational prayers at home. Generally, mosques in most countries are being closed to the public, making it impossible for us to enliven our mosque the way we used to. Nevertheless, many mosques throughout the world have assumed new roles during the lockdown time hence making the functions of mosques continuously alive, albeit in different ways. The altered roles do not only keep the mosque institution functional but also depict its actual functions as enshrined in the teaching of Islam. This is important to provide appropriate portrayal of the mosque functions.